eLingua : Issue 1 : April 2016 / Academy of Language Studies - Mohd Amin, Noraziah; Terng, Hoe Foo; Chone, Liaw Shun; Yih, Mah Boon; Kudus, Nazima Versay; Ab. Rahim, Suzana; Giap, Lim Soo; Muhamad, Sabariah (Academy of Language Studies, 2016)
1. From a Manuscript to a Book Workshop with DBP 2. 6th International Language Learning Conference 2015 3. NLP - a subconscious mind booster approach 4. JSU & JSUB WORKSHOP 5. The Rise of the Web-Based Cognitive Language Instructor 6. E-learning Empowerment through WeCWI Integrated Solutions 7. LANGUAGE CARNIVAL 2015 8. TEC (Testing & Evaluation Committee) degree workshop 9. Vetting Workshop 10. Gotong-Royong Perdana 2015 11. A Report on the UPALS Colloquium 2015 12. UPACARA PERKAHWINAN KAUM CINA 13. Yoi otoshi o 14. WeCWI: The 3rd Medal (Open Category) in Education and Human Development 15. Godzone 16. Mencipta Kebahagiaan Seiring Kehidupan